Guerrilla‐style Defensive Architecture in Detroit: A Self‐provisioned Security Strategy in a Neoliberal Space of Disinvestment. (26th June 2014) - Kinder, Kimberley
Abstract Self‐provisioning has long been an important component of urban political economic processes. However, it has recently become a central feature of grassroots urban governance strategies as well. In tumultuous cities of the twenty‐first century, with governments either unwilling or unable to effectively enforce zoning laws, police neighborhoods or manage infrastructure, some householders have begun performing these services instead. This article examines one subset of self‐provisioning practices that has emerged in southwest Detroit where residents have taken steps to secure abandoned housing as a means of exerting social control over their living environment. These actions embody many contradictions and ethical dilemmas, and the intimate scale of action has left the structural production of disinvestment in places like Detroit largely unchecked. Nevertheless, these guerilla‐style spatial interventions have emerged as critically important response strategies helping residents reduce their vulnerability and stabilize their blocks even as other nearby areas continue to experience decline.